Let
Submit .
Note: Sorry about that, the upper bound is , not .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using the substitution y = ln ( x + 1 ) , then integral becomes A = ∫ 0 1 ( e 2 1 y + 1 ) 2 ( e y − 1 ) 2 sin 2 y e y d y = ∫ 0 1 ( e 2 1 y − 1 ) 2 e y sin 2 y d y = J ( 2 ) − 2 J ( 2 3 ) + J ( 1 ) where J ( a ) can be evaluated by standard integration tricks (double angles, integration by parts): J ( a ) = ∫ 0 1 e a y sin 2 y d y = a ( 4 + a 2 ) 1 [ e a ( 2 + a 2 sin 2 1 − a sin 2 ) − 1 ] and hence A = 6 0 0 1 [ 1 6 e 2 3 ( 9 cos 2 + 1 2 sin 2 − 2 5 ) + 6 0 e ( cos 2 + 2 sin 2 − 5 ) − 7 5 e 2 ( cos 2 + sin 2 − 2 ) − 5 9 ] which makes ⌊ 1 0 0 0 0 A ⌋ = 1 4 0 0 .